2014
DOI: 10.1002/jbmr.2287
|View full text |Cite
|
Sign up to set email alerts
|

Runx2 Regulates Endochondral Ossification Through Control of Chondrocyte Proliferation and Differentiation

Abstract: Synthesis of cartilage by chondrocytes is an obligatory step for endochondral ossification. Global deletion of the Runx2 gene results in complete failure of the ossification process, but the underlying cellular and molecular mechanisms are not fully known. Here, we elucidated Runx2 regulatory control distinctive to chondrocyte and cartilage tissue by generating Runx2 exon 8 floxed mice. Deletion of Runx2 in chondrocytes caused failure of endochondral ossification and lethality at birth. The limbs of Runx2ΔE8/Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
122
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 62 publications
4
122
3
Order By: Relevance
“…We also showed the regulatory role of miR-455-3p as an inhibitor of the expression of Runx2 during chondrogenic differentiation. Considering the important roles of Runx2 in the acceleration of hypertrophic chondrocyte differentiation and endochondral ossification [5,16,17,21,27], we concluded from these data that miR-455-3p potentially alters chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We also showed the regulatory role of miR-455-3p as an inhibitor of the expression of Runx2 during chondrogenic differentiation. Considering the important roles of Runx2 in the acceleration of hypertrophic chondrocyte differentiation and endochondral ossification [5,16,17,21,27], we concluded from these data that miR-455-3p potentially alters chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 79%
“…Runx2 is an important regulator in chondrogenic differentiation and endochondral ossification, and it was shown that Runx2 regulated endochondral ossification by controlling chondrocyte proliferation and differentiation [1,27,[32][33][34]. Runx2 was highly expressed in hypertrophic chondrocytes and osteoblasts [19,27,28], and C/EBPb could enhance Runx2 activity in ossification [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our studies, Sun et al 21 reported a role for SMC autonomous Runx2 in macrophage accumulation and atheromatous lesion formation using a very different Runx2 targeting construct. 41 Their construct targeted exon 8 of the Runx2 gene and produced a functional, truncated Runx2 protein upon Cre-mediated recombination of the floxed-Runx2 allele. 21,41 Importantly, this truncated protein contained an intact Runt DNA binding domain and domains interacting with Runx2 partner proteins, such as CBF and Smad3/4.…”
Section: Discussionmentioning
confidence: 99%
“…41 Their construct targeted exon 8 of the Runx2 gene and produced a functional, truncated Runx2 protein upon Cre-mediated recombination of the floxed-Runx2 allele. 21,41 Importantly, this truncated protein contained an intact Runt DNA binding domain and domains interacting with Runx2 partner proteins, such as CBF and Smad3/4. 21,42 Using SM22aCre to remove Runx2 in vascular SMCs of ApoE À/À mice with this model, the authors found significantly reduced SMC elaboration of RANKL, a tumour necrosis factor family member important for monocyte infiltration and differentiation of mineral-resorbing osteoclasts, 43,44 along with a near complete blockage of monocyte/macrophage recruitment and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%